Design of Internet Problem Report Management System in Diskominfos Bali Province - gede ardi herdiana (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2021)
Abstract- Management system is very important Internal management reporting is a fundamental element of the entire management structure, the most important instrument of control in technology enterprise management. Diskominfos in Bali Province is an agency located in the province of Bali, which have tasks to provide internet bandwidth to all Office in the provincial government area of Bali but the process of manage problem report about internet problem is still manual and not efficient. This study purpose to provide a solution to the problem by designing an information system to simplify the internet report problem management at diskominfos in Bali Province.